PROGRAM PEMBELAJARAN PENGEMBANGAN KEBERANIAN SISWA SEKOLAH DASAR - Farida Sri Indratini, - (2020)
Courage plays an important role in the development of human life as part of a positive character. It needs to be developed in individuals including elementary school students as an effort to improve capability to cope, master, and overcome frightening or difficult situations in the home, school, and friendship environments. It can be conducted through learning program of courage development. This study creates a program and improves the courage of Elementary School students by using pre-experiment method with the one-group pretest-posttest design. The study measurement was instrument of courage. The subjects were 25 students 6.B class of SDN 077 Sejahtera Bandung (149 population numbers). The research data was analyzed by using Wilcoxon. The analysis shows the value score of courage was significant 0.000 (p<0.05). It means that H_a was accepted. Thus, there was a difference before and after intervention of learning program of courage development of elementary school students. The conclusion of this study shows that learning program enables elementary school student's courage to improve. Keyword: learning program, courage, elementary school.